PHOSPHO1 is a skeletal regulator of insulin resistance and obesity - Suchacki, Karla J; Morton, Nicholas M; Vary, Calvin; Huesa, Carmen; Yadav, Manisha C; Thomas, Benjamin J; Turban, Sophie; Bunger, Lutz; Ball, Derek; Barrios-Llerena, Martin E; Guntur, Anyonya R; Khavandgar, Zohreh; et al. (BMC biology, 2020)
BACKGROUND: The classical functions of the skeleton encompass locomotion, protection and mineral homeostasis. However, cell-specific gene deletions in the mouse and human genetic studies have identified the skeleton as a key endocrine regulator of metabolism. The bone-specific phosphatase, Phosphatase, Orphan 1 (PHOSPHO1), which is indispensable for bone mineralisation, has been recently implicated in the regulation of energy metabolism in humans, but its role in systemic metabolism remains unclear. Here, we probe the mechanism underlying metabolic regulation by analysing Phospho1 mutant mice. RESULTS: Phospho1-/- mice exhibited improved basal glucose homeostasis and resisted high-fat-diet-induced weight gain and diabetes. The metabolic protection in Phospho1-/- mice was manifested in the absence of altered levels of osteocalcin. Osteoblasts isolated from Phospho1-/- mice were enriched for genes associated with energy metabolism and diabetes; Phospho1 both directly and indirectly interacted with genes associated with glucose transport and insulin receptor signalling. Canonical thermogenesis via brown adipose tissue did not underlie the metabolic protection observed in adult Phospho1-/- mice. However, the decreased serum choline levels in Phospho1-/- mice were normalised by feeding a 2% choline rich diet resulting in a normalisation in insulin sensitivity and fat mass. CONCLUSION: We show that mice lacking the bone mineralisation enzyme PHOSPHO1 exhibit improved basal glucose homeostasis and resist high-fat-diet-induced weight gain and diabetes. This study identifies PHOSPHO1 as a potential bone-derived therapeutic target for the treatment of obesity and diabetes.
Keywords: Insulin Resistance; glukosa; Glucose; homeostáza; Obesity; Energy Metabolism; energetický metabolismus; Choline; myši; Mice; inzulinová rezistence; obezita; mužské pohlaví; fosfatasy; zvířata; Phosphoric Monoester Hydrolases; Animals; Male; Homeostasis; cholin